1996
DOI: 10.1143/ptp.96.263
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic Effects in Transverse Flow in the Molecular Dynamics Framework

Abstract: In order to investigate relativistic effects we compare the transverse flow calculated using four versions of the QMD approaches with that of the full covariant RQMD approach. We conclude that the simplified RQMD (RQMD/S), which uses a common time coordinate for all particles, can be used instead of RQMD up to 6 GeV /u.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…Additionally, m j /E j , a covariance-related reduction factor for potentials in the Hamiltonian used as in the simplified version of the relativistic quantum molecular dynamics (RQMD/S) model [24,[49][50][51][52]. The squares and circles represent the F2(M ) of the real and mixed events, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, m j /E j , a covariance-related reduction factor for potentials in the Hamiltonian used as in the simplified version of the relativistic quantum molecular dynamics (RQMD/S) model [24,[49][50][51][52]. The squares and circles represent the F2(M ) of the real and mixed events, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In JAM, the nuclear mean-field is implemented based on the RQMD/S [8,10] model. In this approach, the Hamiltonian is given by the sum of the single particle energy: (1) and the equations of motion…”
Section: Modelmentioning
confidence: 99%
“…Many body effects (multiparticle interactions), are implemented in the Boltzmann-Uehling-Uhlenbeck (BUU) [6] and the quantum molecular dynamics (QMD) models [7] in which nuclear meanfield potentials are introduced in the cascade model. In JAM, a nuclear mean-field is implemented [8,9] based on the simplified version of the relativistic quantum molecular dynamics (RQMD/S) approach [10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Ref. [34], with the help of a mean field from RQMD/S [35] and a Jet AA Microscopic Transportation Model (JAM) it has been found that the momentum dependence in the nuclear mean field is important for the understanding of the proton collective flows at AGS and SPS energies.…”
Section: Urqmd Transport Modelmentioning
confidence: 99%